Diseño de un horno eficiente sobre la base del uso de biomasa vegetal: una alternativa para el barrio Pichaló de la ciudad de Latacunga - Salazar Corrales, Marcelo Fabián (2013)
In this paper an experimental and theoretical study of caloric potential in the neighborhood Pichalo eucalyptus, with the aim of being well used in cookingovens of the people, proposing an efficient alternative to simulation design andreducing thus pollution. The literature review highlights the scope of the work performed in methodologies for obtaining calorific value and relationships with other characteristics of wood species used as a source of energy in rural areas ofLatacunga, reflecting economic technical data useful for proposed efficientfurnace. Be part of the pilot study, where a characterization in behavior with the amount of oxygen supplied for combustion and moisture from eucalyptus, from there take place procedures for evaluation and rationalization of plant biomass in the Pichalo neighborhood, in order to contribute to the solutions related to the negative environmental impact and human health, we analyze the most significantincidents energy losses through the simulation of an efficient furnace in the ANSYS program, which involved materials recyclable in combination with different thicknesses of rock wool as insulation selected, obtaining appropriateeucalyptusmass as fuel in households with oven, reducing the social and environmental impacts in the area through research.